The Scarlet Plague - London, Jack, 1876-1916; Grant, Gordon, 1875-1962 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Scarlet Plague" by Jack London is a post-apocalyptic novel published in 1912. Set in 2073, sixty years after a devastating epidemic has nearly wiped out humanity, an elderly survivor travels with his primitive grandsons through the ruins of San Francisco. He recounts memories of civilization before the Red Death struck$1 (Ba world of technology, knowledge, and social order$1 (Bbut struggles to make his grandsons understand a past that seems impossibly distant and unbelievable to them. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Scarlet_Plague
Release date is 2007-06-29
David Widger
Keywords: Science fiction; End of the world -- Fiction; Regression (Civilization) -- Fiction; Epidemics -- Fiction